Corrigendum to “Multimorbidity is associated with fragility fractures in women 50 years and older - Barcelos, Anabela (2023)
Funding Information: The present publication was funded by Fundação para a Ciência e a Tecnologia , IP national support through CHRC ( UIDB/04923/2020 ). Publisher Copyright: © 2023 The Author(s)